2022
DOI: 10.3389/fonc.2022.1010643
|View full text |Cite
|
Sign up to set email alerts
|

Applications of T1 and T2 relaxation time calculation in tissue differentiation and cancer diagnostics—a systematic literature review

Abstract: IntroductionThe purpose of this review was to summarize current applications of non-contrast-enhanced quantitative magnetic resonance imaging (qMRI) in tissue differentiation, considering healthy tissues as well as comparisons of malignant and benign samples. The analysis concentrates mainly on the epithelium and epithelial breast tissue, especially breast cancer.MethodsA systematic review has been performed based on current recommendations by publishers and foundations. An exhaustive overview of currently use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…There was nonsignificant difference between benign lesions and malignant tumors on C 2 . Previous studies have shown that the T2 relaxation time of benign lesions was significantly higher than that of malignant lesions [ 36 , 37 ]. Therefore, we hypothesize that generally higher C 2 and F 2 signal values of benign lesions may be concerned with the higher T2 value and composition of fibroglandular tissue in some types of benign lesions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was nonsignificant difference between benign lesions and malignant tumors on C 2 . Previous studies have shown that the T2 relaxation time of benign lesions was significantly higher than that of malignant lesions [ 36 , 37 ]. Therefore, we hypothesize that generally higher C 2 and F 2 signal values of benign lesions may be concerned with the higher T2 value and composition of fibroglandular tissue in some types of benign lesions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multi‐parametric (mp) MRI is widely used in clinical practice 1–3 for disease detection and evaluation based on the soft‐tissue contrast changes due to altered water magnetization relaxation 4 and diffusion 5 . Recent developments suggest added value in sensitivity and specificity of the quantitative mpMRI protocols, 6,7 particularly for prostate cancer risk stratification 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…MRI is a widely used medical technique that has been in practical use since the 1980s. Quantitative MRI techniques have been developed to assess the relaxation parameters of tissues, [6] including T1 mapping, which quantitatively evaluates and maps the T1 relaxation time for each pixel. T1 mapping displays absolute T1 values, providing a potential method for more objective and accurate tissue property evaluation.…”
mentioning
confidence: 99%